An investigation of physiological correlates of neuroticism during speaking task: A preliminary study - Roslan, N.S. (Institute of Electrical and Electronics Engineers Inc., 2019)
Neuroticism is correlated with negative emotion such as anxiety, fear, depressed mood and loneliness which could be measured using physiological signals such as skin conductance, heart rate, and respiration rates. In this paper, we aim to investigate the correlation between neuroticism and physiological changes during speaking tasks. Eight healthy male subjects were selected including four subjects with high level of neuroticism (neurotic) and four emotionally stable subjects evaluated by Eysenck Personality Inventory (EPI) and Big Five Inventory (BFI) tools. The physiological responses were recorded during baseline measurements (eyes closed and eyes open) and during speaking tasks by using the FlexComp Infiniti encoder with Biograph Infiniti software by Thought Technology Ltd. The results showed that the skin conductance and the heart rate of neurotic subjects were higher than that of the stable subjects during baseline measurements and speaking tasks. In comparison to the baseline, lower respiration rate was exhibited in both stable and neurotic subjects during speaking tasks. However, the neurotic subjects exhibited slight increase in their respiration rates compared to the stable subjects. This paper provides preliminary evidence for physiological responses associated with neuroticism that can shed some light in social interaction studies, stress reduction studies based on mindfulness or emotion regulation to name a few. Â© 2018 IEEE.